Analisis Tantangan dan Peluang Perbankan Syariah dalam Mewujudkan Pembangunan Ekonomi Berkelanjutan - Calvin Alfiansyah; Fauzatul Laily Nisa (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Islamic banking, with principles based on Islamic law, has developed rapidly and become an important part of the global financial system. In the last few decades, Islamic banking has not only been seen as an alternative to conventional banking, but also as an instrument that can make a significant contribution to sustainable economic development. Sharia principles such as the prohibition of riba (interest), maisir (speculation), and gharar (uncertainty) as well as a commitment to social justice and general welfare provide a strong foundation for promoting a sustainable and inclusive economy. This research describes the challenges and opportunities of Islamic banking in realizing sustainable economic development in the form of writing based on literature studies carried out by finding secondary data obtained from literature studies carried out. In expressing the challenges and opportunities of sharia banking in realizing sustainable economic development, it is carried out using the concept of sustainable economic development by looking at three aspects, namely social aspects, economic aspects and environmental aspects.